Coronavirus drug discovery. Volume 2, Antiviral agents from natural products and nanotechnological applications - Egbuna, Chukwuebuka (Amsterdam, Netherlands : Elsevier, 2022)
Coronavirus Drug Discovery, Volume Two: Antiviral Agents from Natural Products and Nanotechnological Applications presents detailed information on drug discovery against COVID-19. Sections in this volume present chapters that focus on the various antiviral agents from natural products that have the propensity to be used as chemical scaffolds for the development of drugs against COVID-19. Also captured are the dietary sources of antioxidant bioactives that may help boost the immune system for the management of COVID-19. Other chapters describe the application of nanotechnology for efficient and effective delivery of drugs against COVID-19. Written by global team of experts, this book is an excellent resource for drug developers, medicinal chemists, pharmaceutical companies in R&D and research institutes in both academia and industry.
Keywords: COVID-19 (Disease) -- Diagnosis; COVID-19 (Disease) -- Prevention